Prevalence of test accommodations for the Medical Council of Canada Qualifying Exam Part I, 2013-2021 - Clarke, Quinten K; Hanes, Julia E (Canadian Medical Education Journal, 2023)
Introduction: Previous articles have highlighted the laborious process of acquiring disability accommodations in medical education. We endeavoured to characterize the trends of test accommodations on the MCCQE Part I. Methods: Data was obtained from the Medical Council of Canada on the number of applicants who attained test accommodations on the MCCQE Part I between 2013 and 2021. The number of test takers for the same period was obtained from the Medical Council of Canada’s Annual Technical Reports; this data was not publicly available for 2013, 2014, or 2021. Prevalence rates and graphs were produced. Results: The number of test takers who attained test accommodations ranged from 35 to 126 between 2013 and 2021. The percentage of test takers who attained test accommodations ranged from 0.89% to 2.01% between 2015 and 2020. Per correspondence with the Medical Council of Canada, no applicant who provided all required documentation was denied test accommodations during this period. Discussion: The number and rate of test takers attaining test accommodations on the MCCQE Part I have increased substantially during this period. It is unclear whether this increase is due to greater rates of students with disabilities, or a reduction in stigma around using test accommodations.